Therapeutic Communication in Providing Psychological and Social Support to Cancer Patients for the 'Surabaya Hebat' Cadre - Septia Iswidyanti, Shinta; Surjaningrum, Endang R. (Newinera Publisher, 2024)
This study aims to enhance the knowledge capacity of Surabaya Hebat Cadres through training in social and psychological support for cancer patients and to improve the palliative care program for cancer patients. The designed community intervention,